Morfogênese, estrutura do pasto e produção de forragem do capim-piatã submetido a estratégias de manejo - Santos, Josimar Nogueira dos (2011)
The animal production systems that rely on the use of grasses as the primary source of nutrients depend on appropriate grazing management to be sustainable. This work aimed to evaluate strategies for cutting the grass Brachiaria brizantha cv. Piatã aiming to define management goals for in southern state of Mato Grosso. The experiment was conducted in the experimental area of the Course of Animal Science, Federal University of Mato Grosso in the period November 2008 to May 2009. Was evaluated four management strategies resulting from the combination of three heights pre-cutting determined by the time when the plants reached 30, 35 and 40 cm, and three intensities of cuts, determined by cutting of the plants a height post-cutting 10, 15 and 20 cm, in the following arrangement: 30/10 (30 cm pre-cut to 10 cm post-cutting), 30/15 (30 cm pre-cut to 15 cm post-cutting) 35/20 (35 cm pre-cut to 20 cm in height post-cutting) and 40/15 (40 cm pre-cut to 15 cm in height post-cut;). Was used a randomized block design with five replicates. The greater number of cuts was observed in plots with the strategies 35/20 and 30/15, which enable cuts to two cycles of more, when compared the targets from management 40/15 and 30/10. The strategies corresponding to the greatest heights of plants in the pre-cut, 40/15 and 35/20, resulted in higher rates of leaf elongation, but also had higher rates of stem elongation and leaf senescence. The lower height of post-cutting strategy in 30/10 resulted in the largest population of tillers, average 830 tillers/m2. The total forage accumulation obtained by the method was similar agronomic strategies for cuts, with an average of 8700 kg DM/ha in the study period. Although the highest rates of forage accumulation were observed in the combinations 40/15 30/10 and 35/20 in there were differences in forage accumulation, due to the cutting intervals and the number of cuts ranging from strategies. In the management corresponding to more frequent cuts, 35/20 and 30/15 provided the highest percentage of leaf blades and lower stems. The highest volumetric densities of forage and leaf were observed in combinations 40/15 and 30/10. However, the lower relations blade:stem observed in these strategies have a negative effect on the structure and quality of forage accumulated. The management of grass-piatã based on goals 35/20 and 30/15 it follows forage with favorable characteristics in animal feed.